Postoperative quality of life, satisfaction, and skin condition after varicose vein surgery - Kath, W.; Bruning, G.; Langenbruch, A.; Augustin, M. (Phlebologie, 2016)
Compression is performed postoperatively with the intention of minimising side effects, such as bleeding and haematoma in the area of operation, as well as postoperative oedema and pain. Compression stocking manufacturing has incorporated the addition of skin care products into the yarn material in recent years. However, the benefits of these products remain controversial. In addition, the length of the compression stocking is disputed in terms of its effectiveness. This effectiveness was investigated in the present study.Before surgery, 160 patients with indication of surgical removal of varicose veins were randomly divided into four groups with different types of compression stockings in each case. In each group, 40 patients received a knee-length stocking (length A–D), thigh-length stocking (length A–G), knee-length stocking with Aloe vera or thigh-length stocking with AV. At time 0 (before surgery), one week and 8 weeks after surgery, skin moisture was measured as an objective parameter, quality of life was determined using the Freiburger questionnaire of quality of life in veinous disease (FLQA-vs), benefit to patients was evaluated using the patient benefit index (PBI-v) and further subjective parameters were investigated with a free-text questionnaire. After surgery, the extent of haematoma was determined using the point count method.After surgery, at both post-operative times, the FLQA-vs decreased significantly (corresponding to a better quality of life), and the PBI-v increased. In the group with Aloe, pruritus was significantly lower, comfort and skin moisture were increased, and skin condition was significantly improved. The extent of haematoma decreased regardless of the length of the stockings.A benefit of AV as a skin care additive was observed. This finding was objectively confirmed based on the skin moisture. The multifactorial quality of life was not affected by the skin care additive. Thigh-length compression stockings did not provide a measurable benefit.In der Kompressionsbestrumpfung wurden in den letzten Jahren Pflegezusätze in das Garnmaterial eingearbeitet, wobei deren Nutzen umstritten ist. In dieser Studie soll der Nutzen des Aloe-vera-Zusatzes und die Länge des Kompressionsstrumpfes auf seine Effektivität hin untersucht werden.Präoperativ wurden 160 Patienten randomisiert in vier Gruppen eingeteilt: Wadenstrumpf und Oberschenkelstrumpf, jeweils mit dem Pflegezusatz Aloe vera (AV) und ohne. Gemessen wurde die Hautfeuchtigkeit, die Lebensqualität und der Patientennutzen. 1 und 8 Wochen postoperativ erfolgte eine erneute Messung mit zusätzlicher Erhebung der Hämatomausprägung.Zu beiden postoperativen Zeitpunkten sinkt der FLQA-vs (Freiburger Fragebogen zur Lebensqualität bei Venenerkrankungen). Der PBI (Patient-Benefit-Index) steigt über beide Messzeitpunkte. In den Gruppen mit Aloe vera war der Juckreiz signifikant niedriger, der Tragekomfort und Hautzustand besser und die Hautfeuchtigkeit signifikant höher. Die Hämatomausprägung sank unabhängig von der Länge der Kompressionstrümpfe.Der Nutzen von Aloe vera ist anhand der Hautfeuchtigkeit belegbar. Die multifaktorielle Lebensqualität wird durch den Pflegezusatz nicht beeinflusst. Kompressionsstrümpfe A–G bringen keinen messbaren Vorteil.
Keywords: Compression therapy; care additives; quality of life; skin condition